Putting subjective well-being to use for ex-ante policy evaluation - H. Xavier Jara; Erik Schokkaert (University of Essex, Institute for Social and Economic Research (ISER), 2016)
Most studies using microsimulation techniques have considered the effect of potential reforms, but only regarding income distribution. However, it has become increasingly recognised, both at the academic and political level, that focusing purely on income provides a limited picture of social progress. We illustrate how ex-ante policy evaluation can be performed in terms of richer concepts of individual well-being, such as subjective life satisfaction and equivalent incomes. Our analysis makes use of EUROMOD, the EU-wide tax-benefit microsimulation model, along with 2013 EUSILC data for Sweden, which for the first time provides information on subjective wellbeing. Our results show that the effect of potential reforms varies widely depending on the well-being concept used in the evaluation. We discuss the normative questions that are raised by this finding.
Keywords: D60; H23; I31; 330; disposable income; satisfaction; equivalent income; microsimulation